2005
DOI: 10.1529/biophysj.104.057851
|View full text |Cite
|
Sign up to set email alerts
|

Different Effects of Long- and Short-Chain Ceramides on the Gel-Fluid and Lamellar-Hexagonal Transitions of Phospholipids: A Calorimetric, NMR, and X-Ray Diffraction Study

Abstract: The effects on dielaidoylphosphatidylethanolamine (DEPE) bilayers of ceramides containing different N-acyl chains have been studied by differential scanning calorimetry small angle x-ray diffraction and (31)P-NMR spectroscopy. N-palmitoyl (Cer16), N-hexanoyl (Cer6), and N-acetyl (Cer2) sphingosines have been used. Both the gel-fluid and the lamellar-inverted hexagonal transitions of DEPE have been examined in the presence of the various ceramides in the 0-25 mol % concentration range. Pure hydrated ceramides e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
88
1
1

Year Published

2009
2009
2019
2019

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 107 publications
(103 citation statements)
references
References 41 publications
13
88
1
1
Order By: Relevance
“…To date, several biophysical studies [e.g., (13)(14)(15)(16)(17)(18)(19)] have focused on the effect of Cer on the properties of model membranes and have demonstrated that Cer increases the global order of the membrane and promotes lateral phase separation in a manner dependent on its acyl chain structure (19)(20)(21). However, no information is currently available on the effect of altering the Cer acyl chain length on the properties of cell membranes.…”
Section: Discussionmentioning
confidence: 99%
“…To date, several biophysical studies [e.g., (13)(14)(15)(16)(17)(18)(19)] have focused on the effect of Cer on the properties of model membranes and have demonstrated that Cer increases the global order of the membrane and promotes lateral phase separation in a manner dependent on its acyl chain structure (19)(20)(21). However, no information is currently available on the effect of altering the Cer acyl chain length on the properties of cell membranes.…”
Section: Discussionmentioning
confidence: 99%
“…Another study re-vealed a specific role for dihydro-C 16:0 -ceramide in the adaptive cardiac tissue response to hypoxia (74). Although certain ceramide species could have different effects on biophysical properties of the membrane lipid bilayer (75), it remains unclear how ceramides containing different fatty acids exert their effects upon cell physiology. These studies suggest that regulated expression of specific CerS in intracellular compartments in conjunction with availability of certain fatty acylCoA species could be an important mechanism for controlling the fatty acid composition of ceramides and their biological effects on cell metabolism.…”
Section: Discussionmentioning
confidence: 99%
“…This notion is based on data from the literature that indicate that sphingolipid N-acyl chain lengths alter the biophysical properties of membranes, including curvature, fluidity, stability, and permeability (58)(59)(60)(61)(62)(63)(64)(65). In particular, it has been shown that genetic ablation of CerS2 in mice promoted membrane fusion and budding (66).…”
Section: Figurementioning
confidence: 99%